(untitled) (Research, Society and Development, 2022)
The use of geotechnologies is increasingly widespread, in this article the use of applied technology in the mapping of heritage assets stands out. The research aimed to apply three-dimensional (3D) modeling in two built patrimonies located on the limits of the Rio Maior Environmental Protection Area, located in the municipality of Urussanga, state of Santa Catarina. The modeling was carried out in order to assist in the preservation, enhancement and dissemination of cultural heritage. The methodological procedures adopted had two processes for the generation of the 3D model: the planning of the photogrammetric flight and the processing of the images. The results showed that the application of digital 3D modeling technology can increase appreciation and recognition and assist in the preservation of built heritage.